2013
DOI: 10.1111/1742-6723.12060
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and outcomes of screening for cardiovascular risk factors in the emergency department

Abstract: Substantial proportions of ED patients have undiagnosed and undertreated hypercholesterolaemia and/or HT. GP referral initiated interventions for many patients with hypercholesterolaemia, but fewer with HT. The ED has potential as a useful venue for the opportunistic screening of hypercholesterolaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…In locations like Tanzania, where the existing primary care system is poorly-equipped to manage the expanding hypertensive population, patients may ultimately end up seeking care in emergency departments (EDs) and inpatient settings. Several studies in high-income countries have established that the emergency department (ED) is an important venue to screen for hypertension, in part because a sustained elevated blood pressure in the ED is highly sensitive for hypertension [1417]. However, it is unclear what role the ED could play in facilitating screening and initiating care for hypertension in LMICs, particularly in SSA [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In locations like Tanzania, where the existing primary care system is poorly-equipped to manage the expanding hypertensive population, patients may ultimately end up seeking care in emergency departments (EDs) and inpatient settings. Several studies in high-income countries have established that the emergency department (ED) is an important venue to screen for hypertension, in part because a sustained elevated blood pressure in the ED is highly sensitive for hypertension [1417]. However, it is unclear what role the ED could play in facilitating screening and initiating care for hypertension in LMICs, particularly in SSA [18].…”
Section: Introductionmentioning
confidence: 99%
“…In SSA, ED care is expensive however it is often the first point of healthcare contact for many people, and occasionally the sole source of medical care, excluding traditional healers [6, 19, 20]. Therefore, the ED may be one of many potential sites to screen patients, educate them about their disease, and ensure linkage to outpatient follow-up care [17, 21]. However, in SSA, even preliminary epidemiological data concerning the burden of hypertension and linkage to care from the ED are severely lacking.…”
Section: Introductionmentioning
confidence: 99%
“…There was a large range in population size; McNaughton et al 18 had by far the most participants at nearly 702 million, the implications of which are discussed later. Fifteen of the studies reported an estimate of prevalence [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] and the persistence of hypertension in eight studies within the ED 20,23,26,31,[33][34][35][36] and 12 outside of ED. 19,20,22,28,30,31,[36][37][38][39][40][41] Follow-up attendance was reported in eight studies 20,22,29,30,33,36,39,40 and three reported the prognostic performance of hypertension for CVD.…”
Section: Search Results Smentioning
confidence: 99%
“…Exact likelihood estimation 19,20,22,28,30,31,[36][37][38][39][40][41] F I G U R E 5 Meta-analysis forest plot of the proportion of attendance at follow-up for hypertension. Exact likelihood estimation 20,22,29,30,33,36,39,40 However, given our pooled estimates of 41% attendance at followup this might fail to capture a significant proportion of patients and indicate that a different model is needed. Consequently, acting within the ED visit could be beneficial, avoiding this loss to followup.…”
Section: Discussionmentioning
confidence: 99%
“…However, single cardiovascular risk factors are still being measured without being part of a structured risk management programme, for example in occupational health, for research purposes, or in incidentally offered health checkups at pharmacies or by private companies. 46 In the Netherlands, every year 1,875,000 individuals undergo health checks outside primary care. 7 In addition, another 317,000 individuals are involved each year in research 8 in which risk factors are often measured.…”
Section: Introductionmentioning
confidence: 99%